Inter-therapist agreement in classifying patients with cervical radiculopathy and patients with non-specific neck arm pain - Tampin, Brigitte; Briffa, Kathy; Hall, Toby; Lee, G.; Slater, Helen (Elsevier, 2012)
Identification of differences in clinical presentation and underlying pain mechanisms may assist the classification of patients with neck–arm pain which is important for the provision of targeted best evidence based management. The aim of this study was to: (i) assess the inter-examiner agreement in using specific systems to classify patients with cervical radiculopathy and patients with non-specific neck–arm pain associated with heightened nerve mechanosensitivity (NSNAP); (ii) assess the agreement between two clinical examiners and two clinical experts in classifying these patients, and (iii) assess the diagnostic accuracy of the two clinical examiners. Forty patients with unilateral neck–arm pain were examined by two clinicians and classified into (i) cervical radiculopathy, (ii) NSNAP, (iii) other. The classifications were compared to those made independently by two experts, based on a review of patients' clinical assessment notes. The experts' opinion was used as the reference criterion to assess the diagnostic accuracy of the clinical examiners in classifying each patient group. There was an 80% agreement between clinical examiners, and between experts and 70%–80% between clinical examiners and experts in classifying patients with cervical radiculopathy (kappa between 0.41 and 0.61). Agreement was 72.5%–80% in classifying patients with NSNAP (kappa between 0.43 and 0.52). Clinical examiners' diagnostic accuracy was high (radiculopathy: sensitivity 79%–84%; specificity 76%–81%; NSNAP: sensitivity 78%–100%; specificity 71%–81%). Compared to expert opinion, clinicians were able to identify patients with cervical radiculopathy and patients with NSNAP in 80% of cases, our data supporting the reliability of these classification systems.